An Uncommon Presentation of a Ruptured Right Common Iliac Artery Infected Pseudoaneurysm as Deep Vein Thrombosis: A Case Report and Literature Review - Deshan Mario Gomez; Lumini Edirisuriya; Praneeth Athukorale; Thushan Gooneratne (Vascular Specialist International)
Isolated iliac artery pseudoaneurysms are extremely rare and typically asymptomatic. However, symptoms may arise from rupture or compression of adjacent structures, such as the ureter, bowel or deep veins. A 46-year-old male presented with right lower limb swelling and preceding lower abdominal pain of 6 months. Duplex imaging showed iliofemoral deep vein thrombosis. Blood tests showed neutrophil leukocytosis and elevated inflammatory markers. Contrast-enhanced computed tomography demonstrated a large eccentric, irregular right common iliac artery pseudoaneurysm with hydronephrosis, hydroureter, and inferior vena cava compression. Based on the radiological and biochemical investigations, a tentative diagnosis of infected iliac artery pseudoaneurysm was made. The patient was successfully managed with endovascular stent grafting. Deep vein thrombosis is a rare presentation of a infected iliac artery pseudoaneurysm. Early referral and timely intervention are crucial for achieving optimal outcomes.